Trends in alcohol and marijuana detected in homicide victims in 9 US states: 2004-2016 - Oybek Nazarov; Guohua Li (BMC, 2020)
Abstract Background Use of alcohol and other drugs is a major risk factor for assaultive injuries and violent deaths. The purpose of this study was to examine the time trends in the prevalence of alcohol and marijuana detected in homicide victims. Methods We analyzed toxicological testing data for homicide victims (n = 12,638) from the 2004-2016 National Violent Death Reporting System in 9 US states (Colorado, Georgia, Massachusetts, New Jersey, Oregon, Rhode Island, South Carolina, Virginia, and Wisconsin). We used the Cochran-Armitage test for trend to assess the statistical significance of changes in the prevalence of alcohol and marijuana detected in these homicide victims during the study period. Results Overall, 37.5% of the homicide victims tested positive for alcohol, 31.0% positive for marijuana, and 11.4% positive for both substances. During the study period, the prevalence of marijuana increased from 22.3% (95% confidence interval [CI] = 19.6, 25.0) in 2004 to 42.1% (95% CI = 39.2, 44.9) in 2016 (Z = -15.7; P < .001) while the prevalence of alcohol declined slightly (Z = 1.5; P = 0.143). Marked increases in the prevalence of marijuana were observed in both sexes and across age and racial groups. Conclusions Marijuana is increasingly detected in homicide victims irrespective of demographic characteristics. Further research is needed to assess the causal role of marijuana use and concurrent use of marijuana and alcohol in homicide victimization.